Clear as a bell: The influence of analogies on the development of cross-understanding in design teams. Issue 7 (8th October 2018) - Graff, Daniel; Clark, Mark A.
Abstract : Purpose: This study reviews the construct of analogy as an individual communication mode, examining its relationship with cross-understanding in knowledge-diverse teams. The authors theorize that analogy use enhances team information processing beyond mere communication frequency through bridging knowledge differences across team members. The authors propose that analogies will have a direct relationship to knowledge application, and an indirect effect via cross-understanding. However, communication frequency will have only an indirect effect on knowledge application through cross-understanding. Design/methodology/approach: The authors sampled a 49-member team with 14 subteams, yielding 146 usable dyadic relationships. Two mediation models were estimated while using linear mixed-effect models in SPSS. Findings: The results confirm the importance of analogies and cross-understanding in teams, generally supporting the hypotheses. Mere communication frequency was not related to knowledge application, indicating that "how you say it" may be more important than how often a team member speaks. Research limitations/implications: This research explored these constructs through a three-week project in a sample of graduate students working with a real-world client. Future research could explore the validity of this model in other organizational settings and test the analogy construct on the team level. Practical implications: The effectiveness of team member communication should be measured not only as frequency but also in terms of analogies to transmit meaning. Originality/value: This paper contributes to an understanding of teams as information processors by building empirical support for the utility of analogical communication in design teams, establishing the relationship of analogies to cross-understanding and knowledge application.